Sustainable tourism strategies in the Palomino township, department of La Guajira (2023)
i) Introduction: Tourism is one of the most relevant economic activities worldwide and a potential engine for the development of developing communities; ii) objective: This article aims to propose sustainable tourism strategies in the Palomino township, department of La Guajira within the framework of economic reactivation after the covid 19 pandemic. iii) methodology: The research is based on a study with a mixed approach and descriptive scope, where questionnaire surveys were applied to 47 hostels/hotels located in Palomino and registered with the Chamber of Commerce of La Guajira. The data were statistically analyzed in SPSS. iv) results: Among the most relevant findings, it is considered that the problem of coastal erosion, the lack of tourist infrastructure and the poor coverage of public services are a barrier to sustainability in the territory; v) conclusions: Finally, actions are recommended to strengthen the economy, preserve identity and conserve na-tural and environmental resources, promote the destination, implement digital marketing strategies and enhance big data that accelerate economic recovery after the crisis generated by the COVID -19 pandemic.